Evaluation of the anti-inflammatory effect of infliximab in a mouse model of acute asthma - Deveci, Figen; Muz, M. Hamdi; Ilhan, Nevin; Kirkil, Gamze; Turgut, Teyfik; Akpolat, Nusret (Wiley, 2008)
Background and objective: To evaluate the potential role of anti-tumour necrosis factor (TNF)-alpha mAb (infliximab) on the inflammatory response in a mouse model of acute asthma. Methods: BALB/c mice received intraperitoneal (i.p.) ovalbumin (OVA) on days 0 and 14, 100 mu g of OVA intranasally on day 14 and 50 mu g of OVA intranasally on days 25, 26 and 27. The low-dose (2.5 mg/kg) and high-dose (6.25 mg/kg) infliximab groups received i.p. infliximab before each i.p. sensitization and on challenge days 1, 6, 13, 20 and 27. The control group received i.p. injections of normal saline with alum on days 0 and 14 and normal saline without alum on days 14, 25, 26 and 27. Results: There were statistically significant decreases in the numbers of BAL fluid (BALF) neutrophils, eosinophils, as well as lung eosinophils in both the low- and high-dose infliximab groups when compared with the control OVA sensitized/challenged group. The lower dose of infliximab did not alter lung neutrophil counts, but a marked decrease was seen with the high dose of infliximab. After treatment with low and high doses of infliximab, BALF levels of regulated on activation normal T cell expressed and secreted (RANTES), granulocyte macrophage-colony stimulating factor (GM-CSF), TNF-alpha, IL-6, macrophage inflammatory protein (MIP)-2, and levels of RANTES, IL-4, GM-CSF, TNF-alpha, IL-6 and MIP-2 in lung tissue were significantly decreased when compared with the control OVA sensitized/challenged group. There was a significant decrease in BALF IL-4 only in the high-dose infliximab group. Conclusions: These results show that an anti-TNF-alpha mAb has a considerable anti-inflammatory effect on allergen-induced lung inflammation in an animal model of acute asthma.
Keywords: anti-tumour necrosis factor alpha; asthma; chemokine; cytokine